Intelligent agriculture : developing a system for monitoring and controlling production - Maldonado-Guzmán, Gonzalo; Garza-Reyes, Jose Arturo; Solano-Romo, Lizeth Itziguery (Emerald points., 2019)
Intelligent Agriculture: Developing a System for Monitoring and Controlling Production examines the development of Wireless Sensor Network (WSN) technology designed to monitor and control agriculture production. The book is divided into four sections which illustrate the innovative technology of this product. Section One explores the consumer's discovery of the product and includes a benchmark analysis of the WSN against other similar technologies alongside a technological roadmap, intellectual property analysis and value proposal. Sections Two and Three demonstrate the development of WSN technology in relation to system architecture and software application. Finally, Section Four outlines concept activities used to test the WSN technology and its solutions.An illuminating resource for academics and professionals within the fields of agriculture and agribusiness, this volume will also serve as a helpful guide for other technological sectors as a reference for the development of new technologies.